"It makes you feel like they've actually put effort into it." Students' perceptions of screen-capture video feedback on assignments on a social science course - Pryke, Sam; Rees, Michael; Witton, Gemma (Interactive learning environments, 2024)
This article is the first to examine the use of screen-capture video feedback on student assignments on a social science degree at a British university. It is based on qualitative, focus group, research with students who received one or more video recordings on their academic work over the period 2019-2021. The article first places video feedback in the wider context of research on the subject. Our literature review suggests that whilst video does not herald a pedagogic revolution, it is a considerable advance on orthodox written feedback. Our findings are that students prefer video recordings because they provide (1) an interpersonal aspect to feedback; (2) more extensive, detailed, nuanced and directed coverage of their work than with written comments; (3) a more credible appreciation of their grade. Our discussion ends with a summary of our findings and a breakdown of the benefits and constraints of video feedback.